Comparative efficacy and safety of the Ambu® AuraOnce™ laryngeal mask airway during general anaesthesia in adults: a systematic review and meta‐analysis. (7th May 2014) - Baidya, D. K.; Chandralekha; Darlong, V.; Pandey, R.; Maitra, S.; Khanna, P.
Summary Previous comparisons between the Ambu® AuraOnce™ and other laryngeal mask airways have revealed different results across various clinical studies. We aimed to perform a systematic review with meta‐analysis on the efficacy and safety of the AuraOnce compared with other laryngeal mask airways for airway maintenance in adults undergoing general anaesthesia. Our search of PubMed, PubMed Central, Scopus and the Central Register of Clinical Trials of the Cochrane Collaboration yielded nine randomised controlled trials eligible for inclusion. Comparator laryngeal mask airways were the LMA Unique™ (four trials), the LMA Classic® (five trials) and the Portex® Soft Seal® (three trials). The AuraOnce provided an oropharyngeal leak pressure higher than the LMA Unique (304 participants, mean (95% CI) difference 3.1 (1.6–4.7) cmH2O, p < 0.0001) and equivalent to the LMA Classic. The Soft Seal provided a higher leak pressure than the AuraOnce (229 participants, mean (95% CI) difference 3.5 (0.4–6.7) cmH2O, p = 0.03). Insertion was significantly faster with the AuraOnce than the LMA Unique (304 participants, mean (95% CI) difference 5.4 (2.1–8.71) s, p = 0.001) and Soft Seal (229 participants, mean (95% CI) difference 9.5 (3.0–15.9) s, p = 0.004), but similar to the LMA Classic. The first‐insertion success rate of the AuraOnce was equivalent to the LMA Unique, LMA Classic and Soft Seal. We found a higher likelihood of bloodstaining on the cuff with the Soft Seal and a higher incidence of sore throat with the LMA Classic. We conclude that the AuraOnce is an effective alternative to the LMA Classic and LMA Unique, and easier to insert than all three other devices studied.